CLOUD COMPUTING AS A CREATIVE APPROACH OF HUMAN CAPITAL MANAGEMENT - Singh, Ashutosh; Mishra, Amitabh (International Journal of Psychosocial Rehabilitation, 2020)
Cloud computing is the latest and burning topic for individuals, academician, researchers and the business community. Cloud computing is a integration of abstract, highly scalable and regulated resources that is capable of hosting customer applications and is paid according to usage. This computational paradigm was viewed as a key factor for gaining competitive advantage in the globalized marketplace as well as sustainability. In addition, human resources managers often use cloud computing technology for their daily operations, such as searching for resumes, tracking applications, building mobile human capital, improving flexibility, monitoring efficiency, fast decision-making, and others. On the other hand, some of the problems that arise when taking advantage of cloud computing are privacy concerns, protection concerns, data misuse and data loss. Implementation of appropriate authorization, validation, tracking, filter application and others will help to address cloud computing challenges and achieve long-term sustainability on the global marketplace. HR and cloud computing model collaboration would thus help to improve an organization’s efficiency, innovativeness, and intellectual capital.